2018
DOI: 10.1186/s12931-018-0735-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATP-sensitive potassium channels on hypoxic pulmonary vasoconstriction in endotoxemia

Abstract: BackgroundATP-regulated potassium channels (KATP) regulate pulmonary vascular tone and are involved in hypoxic pulmonary vasoconstriction (HPV). In patients with inflammation like sepsis or ARDS, HPV is impaired, resulting in a ventilation-perfusion mismatch and hypoxia. Since increase of vascular KATP channel Kir6.1 has been reported in animal models of endotoxemia, we studied the expression and physiological effects of Kir6.1 in murine endotoxemic lungs. We hypothesized that inhibition of overexpressed Kir6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In line with other studies, a strong HPV was found in buffer-perfused isolated mouse lungs of healthy animals [14,15]. Consistent with previous experiments, a distinctive reduction of HPV was observed in lungs of endotoxemic mice [4,16].…”
Section: Discussionsupporting
confidence: 92%
“…In line with other studies, a strong HPV was found in buffer-perfused isolated mouse lungs of healthy animals [14,15]. Consistent with previous experiments, a distinctive reduction of HPV was observed in lungs of endotoxemic mice [4,16].…”
Section: Discussionsupporting
confidence: 92%
“…This beneficial effect of HPV has been shown to be inhibited in experimental models of oleic acid, bleomycin, or endotoxin-induced ALI (Sylvester et al, 2012 ), underscoring the important role that HPV has in matching ventilation/perfusion. Herein, studies in mice have revealed that inhibition of ATP-regulated potassium channel Kir6.1, which is elevated after endotoxemia, was able to restore HPV in mice; however, the effects on lung inflammation were not assessed (Turzo et al, 2018 ). However, prolonged HPV can lead to the development of PH and high-altitude induced pulmonary edema (HAPE) which is characterized by patchy peripheral distribution of edema (Bartsch, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors of voltage-dependent potassium (K v ) channels, such as 4-aminopyridine, are possible sensitisers of hypoxic K v -channel inhibition and restored HPV in isolated lungs in LPS-preconditioned mice [31]. Inhibition of the vasodilatory K ATP channels with PNU-37883A was found to restore HPV in isolated lungs from endotoxaemic mice, while HPV among non-endotoxaemic controls was not altered [32]. However, a previous clinical trial with the K ATP channel inhibitor glibenclamide, focussing on systemic hypotension, failed [33].…”
Section: Relative Hyperperfusion Of Poorly Ventilated Lung Areas (Low V/q Areas)mentioning
confidence: 99%